Structures of the L27 Domain of Disc Large Homologue 1 Protein Illustrate a Self-Assembly Module. - Ghosh, A.; Ramagopal, U.A.; Bonanno, J.B.; Brenowitz, M.; Almo, S.C. (Biochemistry, 2018)
Disc large 1 (Dlg1) proteins, members of the MAGUK protein family, are linked to cell polarity via their participation in multiprotein assemblies. At their N-termini, Dlg1 proteins contain a L27 domain. Typically, the L27 domains participate in the formation of obligate hetero-oligomers with the L27 domains from their cognate partners. Among the MAGUKs, Dlg1 proteins exist as homo-oligomers, and the oligomerization is solely dependent on the L27 domain. Here we provide biochemical and structural evidence of homodimerization via the L27 domain of Dlg1 from Drosophila melanogaster. The structure reveals that the core of the dimer is formed by a distinctive six-helix assembly, involving all three conserved helices from each subunit (monomer). The homodimer interface is extended by the C-terminal tail of the L27 domain of Dlg1, which forms a two-stranded antiparallel ?-sheet. The structure reconciles and provides a structural context for a large body of available mutational data. From our analyses, we conclude that the observed L27 homodimerization is most likely a feature unique to the Dlg1 orthologs within the MAGUK family.